Enhancing β-cyclodextrin production by immobilization of recombinant escherichia coli on hollow fiber membrane: Screening the reaction parameters by full factorial design - Rohaida, Che Man; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Sulaiman; Yamani, Laura Navika; Zatul Iffah, Mohd Arshad (Semarak Ilmu Publishing, 2025)
Cyclodextrin (CD) is an organic compound that is nontoxic and has hydrophobic interior and hydrophilic peripheries, making it soluble in water. It is widely used in pharmaceuticals, food, and agrochemicals due to its unique characteristics. CD is produced via enzymatic conversion from starch, utilizing the cyclodextrin glucanotransferase (CGTase).The industrial production of β-CD requires a high yield of β-CGTase, but the output from Bacillussp. is insufficient to meet this demand. Recombinant β-CGTase expressed in E. coliwas utilized to address the low yield of CGTase from Bacillussp.However, cell lysis and plasmid instability have been significant obstacles in the excretion and production of recombinant β-CGTase in E. coli.Cell immobilization has been suggested as a strategy to enhance β-CGTase excretion and β-CD production while preserving cell stability. The recombinant E. coliwas immobilized using a hollow fiber membrane as a support. Many factors affect β-CD production and β-CGTase excretion in the immobilization system,such as temperature, pH, substrate concentration, reaction time and agitation rate. Thus, the objective of this study is to screen the significant reaction parameters that have a significant effect on β-CD production and β-CGTase excretion, using a full factorial design (FFD). A 25FFD was applied, and the results were analyzed statistically. Substrate concentration and temperature were found to be the key factors of β-CD synthesis and β-CGTase excretion by immobilized cells. In conclusion, the findings of this study indicate that FFD is a promising approach to reduce the number of experiments and screen the significant parameters for the production of the desired product.